Expression, Solubilization, and Purification of Bacterial Membrane Proteins. (2nd February 2016) - Jeffery, Constance J.
Abstract: Bacterial integral membrane proteins play many important roles, including sensing changes in the environment, transporting molecules into and out of the cell, and in the case of commensal or pathogenic bacteria, interacting with the host organism. Working with membrane proteins in the lab can be more challenging than working with soluble proteins because of difficulties in their recombinant expression and purification. This protocol describes a standard method to express, solubilize, and purify bacterial integral membrane proteins. The recombinant protein of interest with a 6His affinity tag is expressed in E. coli . After harvesting the cultures and isolating cellular membranes, mild detergents are used to solubilize the membrane proteins. Protein‐detergent complexes are then purified using IMAC column chromatography. Support protocols are included to help select a detergent for protein solubilization and for use of gel filtration chromatography for further purification. © 2016 by John Wiley & Sons, Inc.